Analysis of leaf morphology and photosynthesis in deletion mutants of rice (Oryza sativa L.) - Smillie, Ian R.A. (2012)
As a plant operating the C3 photosynthetic pathway and commonly grown under tropical conditions of high light intensity and temperature, rice (Oryza sativa) displays high levels of photorespiration, to the detriment of photosynthetic efficiency. For this reason it is thought that improvements to net photosynthesis via an increased photosynthetic efficiency could provide significant gains in terms of grain yield. There is great interest in 1. Introducing CO2 concentrating mechanisms into C3 crop plants such as the C4 photosynthetic pathway in order to facilitate enhanced photosynthetic efficiency. This requires an understanding of C3 and C4 leaf development and establishing whether there is sufficient plasticity in the rice genome to produce plants with C4-like properties. 2. Improving existing C3 photosynthesis by means of increasing leaf thickness, vein density and investigation of the impacts of mesophyll cell size.